An algebraic expression f(x) of the form f(x) = a_{0} + a_{1}x + a_{2}x^{2 }+ ......+ anxn, where a_{0}, a_{1}, a_{2}.......an are real numbers and all the index of x are non-negative integers is called **polynomials **in x and the highest Index n in called the degree of the **polynomial,** if

a_{n} ≠ 0.

Any non-zero number is regarded as a polynomial of degree zero or zero degree polynomial. For example, f(x) = a, where a ≠ 0 is a zero degree polynomial, since we can write f(x) = a as f(x) = ax0.

A polynomial of degree zero is called a constant polynomial. e.g. f(x) = 7.

A polynomial of degree 1 is called a linear polynomial.

e.g. p(x) = 4x - 3 and f(t) = √3t + 5 are linear polynomials.

A polynomial of degree 2 is called quadratic polynomial.

e.g. f(x) = 2x2 + 5x –3/5 and g(y) = 3y2 – 5 are quadratic polynomials with real coefficients.

If f(x) is a polynomial and α is any real number, then the real number obtained by replacing x by α in f(x) is called the value of f(x) at x = α and is denoted by f(α).

e.g. Value of p(x) = 5x^{2} - 3x + 7at x = 1 will be

∴ p(1) = 5(1)^{2} - 3(1) + 7

= 5 - 3 + 7 = 9

A real number α is a zero of polynomial f(x) if f(α) = 0.

The zero of a linear polynomial ax + b is -b/a . i.e.

Geometrically zero of a polynomial is the point where the graph of the function cuts or touches x-axis.

When the graph of the polynomial does not meet the x-axis at all, the polynomial has no real zero.

In algebraic or in set theoretic language the graph of a polynomial f(x) is the collection (or set) of all points (x, y), where y = f(x). In geometrical or in graphical language the graph of a polynomial f(x) is a smooth free hand curve passing through points x_{1}, y_{1}), (x_{2}, y_{2}), (x_{3}, y_{3}), ..... etc. where y_{1}, y_{2}, y_{3},.... are the values of the polynomial f(x) at x_{1}, x_{2}, x_{3},.... respectively.

In order to draw the graph of a polynomial f(x), follow the following algorithm.

Step I: Find the values y_{1}, y_{2,} ...... yn of polynomial f(x) on different points x_{1}, x_{2}, ....... xn………… and prepare a table that gives values of y or f(x) for various values of x.

x: |
x |

y = f(x) |
y |

**Step II: **Plot that points (x_{1}, y_{1}), (x_{2}, y_{2}), (x_{3}, y_{3}),.....(x_{n}, y_{n}).... on rectangular co-ordinate system. In plotting these points use different scales on the X and Y axes.

**Step III:** Draw a free hand smooth curve passing through points plotted in step 2 to get the graph of the polynomial f(x).

Consider a linear polynomial f(x) = ax + b, a ≠ 0 Graph of y = ax + b is a straight line. That in why f(x) = ax + b) is called a linear polynomial. Since two points determine a straight line, so only two points need to plotted to draw the line y = ax + b. The line represented by y = ax + b crosses the X-axis at exactly one point, namely.

1. Draw the graph of the polynomial f(x) = 2x - 5. Also, find the coordinates of the point where it crosses X-axis.

**Sol. **Let y = 2x - 5.

The following table list the values of y corresponding to different values of x.

x |
1 |
4 |

y |
-3 |
3 |

The points A (1, - 3) and B (4, 3) are plotted on the graph paper on a suitable scale. A line is drawn passing through these points to obtain the graphs of the given polynomial.

Let a,b,c be real numbers and a ≠ 0. Then f(x) = ax2 + bx + c is known as a quadratic polynomial in x. Graph of the quadratic polynomial i.e. he curve whose equation is y = ax2 + bx + c, a ≠ 0 Graph of a quadratic polynomial is always a parabola.

Let y = ax^{2} + bx + c, where a ≠ 0

⇒ 4ay = 4a^{2}x^{2} + 4abx + 4ac

⇒ 4ay = 4a^{2}x^{2} + 4abx + b^{2} – b^{2} + 4ac

⇒ 4ay = (2ax + b)^{2} – (b^{2} - 4ac)

⇒ 4ay + (b2 – 4ac) = (2ax + b)^{2} ⇒ 4ay + (b^{2} – 4ac) = 4a^{2 }(x + b/2a)^{2}

where D = b^{2} - 4ac is the discriminate of the quadratic equation.

**Remarks:**

Shifting the origin at , we have X = x - and Y = y -

Substituting these values in (i), we obtain

Y = aX^{2} ....(ii)

which is the standard equation of parabola

Clearly, this is the equation of a parabola having its vertex at .

The parabola opens upwards or downwards according as a > 0 or a < 0.

The graphs of y = ax^{2} + bx + c are given in figure. Identify the signs of a, b and c in each of the following:

(i) We observe that y = ax^{2} + bx + c represents a parabola opening downwards. Therefore, a < 0. We observe that the turning point of the parabola is in first quadrant where

Parabola y = ax^{2} + bx + c cuts y-axis at Q. On y-axis, we have x = 0.

Putting x = 0 in y = ax^{2} + bx + c we get y = c.

So, the coordinates of Q are (0, c). As Q lies on the positive direction of y-axis. Therefore, c > 0.

Hence, a < 0, b > 0 and c > 0.

(ii) We find that y = ax^{2} + bx + c represents a parabola opening upwards. Therefore, a > 0 The turning point of the parabola is in fourth quadrant.

Parabola y = ax^{2} + bx + c cuts y-axis at Q and y-axis. We have x = 0. Therefore, on putting x = 0 in y = ax^{2} + bx + c we get y = c.

So, the coordinates of Q are (0, c). As Q lies on negative y-axis. Therefore, c < 0.

Hence, a > 0, b < 0 and c < 0.

(iii) Clearly, y = ax^{2} + bx + c represents a parabola opening upwards.

Therefore, a > 0. The turning point of the parabola lies on positive direction of x-axis.

The parabola y = ax^{2} + bx + c cuts y-axis at Q which lies on positive y-axis. Putting

x = 0 in y = ax^{2} + bx + c we get y = c. So, the coordinates of Q are (0, c). Clearly, Q lies on OY.

∴ c > 0.

Hence, a > 0, b < 0, and c > 0.

(iv) The parabola y = ax^{2} + bx + c opens downwards. Therefore, a < 0.

The turning point of the parabola is on negative x-axis,

Parabola y = ax^{2} + bx + c cuts y-axis at Q (0, c) which lies on negative y-axis. Therefore, c < 0.

Hence, a < 0, b < 0and c < 0.

(v) We notice that the parabola y = ax^{2} + bx + c opens upwards. Therefore, a > 0.

Turning point of the parabola lies in the first quadrant.

As Q (0, c) lies on positive y-axis. Therefore, c > 0.

Hence, a >0, b < 0 and c > 0.

(vi) Clearly, a < 0

Turning point of the parabola lies in the fourth quadrant.

As Q (0, c) lies on negative y-axis. Therefore, c < 0.

Hence, a < 0, b> 0 and c < 0.